Chronic changes developing in the hydronephrotic and contralateral kidneys during unilateral ureteral obstruction in rats - Kutlu, Tuncer; Kaya, Ufuk; Yurtal, Ziya; Güvenç, Mehmet; Özkan, Hüseyin; Etyemez, Muhammed; Alakuş, İbrahim; Keçeli, Hasan Hüseyin (Springer Science and Business Media LLC, 2025)
Animal models of chronic kidney disease are important experimental tools used to validate new mechanisms and potential innovations, as well as to investigate therapeutic interventions before clinical trials in humans. This study aimed to determine the chronic changes occurring in the obstructed kidneys (OK) and the contralateral (CL) kidneys in unilateral ureteral obstruction (UUO) in rats.In the study, three groups (n:6) were formed. It was observed that dilated tubules decreased at 28 days compared to 14 days, while mononuclear cell infiltration and fibrosis increased. In the CL kidneys, glutathione (GSH) was lower compared to the control group (CG) at 14 days; at 28 days, malondialdehyde (MDA) was elevated, and GSH and catalase (CAT) levels were reduced. Nuclear factor erythroid 2-related factor 2 (NRF-2) protein expression was lower in the OK compared to the CL kidneys at both 14 and 28 days. NRF-2 gene expression was lower in the OK only at 28 days compared to the CG. However, in the CL kidneys, NRF-2 gene expression was higher at both 14 and 28 days compared to the CG. Cyclooxygenase-2 (COX-2) protein levels showed a significant increase in both the OK and CL kidneys at 14 days. COX-2 gene expression increased in the OK at 14 days compared to the CG. BAX protein levels were lower in the OK at 28 days compared to both the CG and CL kidneys. BCL-2 protein levels were lower in the OK compared to the CL kidneys at both 14 and 28 days.This study has identified changes in both the OK and CL kidneys, providing significant data for potential therapeutic, supportive, or protective research aimed at treating these kidneys.
Keywords: Male; NF-E2-Related Factor 2; Hydronephrosis; Kidney; Catalase; Glutathione; Fibrosis; Rats; Disease Models, Animal; Oxidative Stress; Cyclooxygenase 2; Malondialdehyde; Animals; Renal Insufficiency, Chronic; Ureteral Obstruction